HUBUNGAN EKONOMI MAKRO DAN RETURN ON ASSET (ROA) BANK NUSA TENGGARA BARAT SYARIAH DALAM PENDEKATAN VECTOR ERROR CORRETION MODEL (VECM) - Ahmad Ridho Hidayat (Yayasan Nusantara Hasana Berdikari, 2025)
Banking activity is affected by internal variables and external variables, variable macro economics is a variable that affects banking development.This probe aims to see the variable relationship of macro economy with return on asset banking using the approach vector error correction model (VECM).By taking skunder data at an Ntb sharia bank.The results of this study in the long-term approach of the vecm variable economy macro (birate, inflation and curs ) affect roa bank ntb sharia period 2019-2024.Whereas in the short term model, there is no causality inter-variable relationship., but in fortet analysis of variable decomposition error (FEVD ) and IRF (impulse response function) shows the link between variables in short term, Because the variable macro changes that occur will result in overall banking activity.